Literature Review on Factors Influencing Employee Performance: Variables of Motivation, Discipline, and Job Satisfaction - Saputra, Edward Bayu; Yosepha, Sri Yanthy (Dinasti Publisher, 2025)
Employee performance is a crucial factor in determining an organization's success and sustainability. Understanding the factors influencing performance helps design strategies to enhance employee productivity and achieve organizational goals. This article examines the role of motivation, discipline, and job satisfaction as interrelated variables affecting employee performance. Based on a literature review, this study finds that: (1) motivation has a direct and significant impact on employee performance, serving as a driving force for goal achievement; (2) discipline fosters consistency and adherence to organizational standards, positively influencing performance outcomes; and (3) job satisfaction acts as an intervening variable linking motivation and discipline to overall performance levels. This study highlights the importance of these three variables in designing effective human resource strategies, contributes to academic discourse, and provides direction for future empirical research.